2020
DOI: 10.3390/su12125100
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Processing Parameters on the Products of Hydrothermal Carbonization of Corn Stover

Abstract: Corn stover is an abundant and underused source of lignocellulose waste biomass that can be transformed into a high-quality energy resource using hydrothermal carbonization (HTC). This investigation has focused on the effect of processing parameters on the products of HTC—namely solid fuel or hydrochar and liquid and gas fractions. HTC was conducted in a temperature-controlled small batch reactor with corn stover and deionized water under oxygen-free conditions obtained by pressurizing the reactor headspace wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
4
23
0
3
Order By: Relevance
“…However, the present study focuses on the HTL of wood chips, so we did not examine the gaseous components in detail. Other groups conducting similar research confirmed that the yield of hydrogen, carbon dioxide, carbon monoxide, and methane in the gas fraction are higher at supercritical conditions than at subcritical conditions [2].…”
Section: Mass Balancementioning
confidence: 82%
See 2 more Smart Citations
“…However, the present study focuses on the HTL of wood chips, so we did not examine the gaseous components in detail. Other groups conducting similar research confirmed that the yield of hydrogen, carbon dioxide, carbon monoxide, and methane in the gas fraction are higher at supercritical conditions than at subcritical conditions [2].…”
Section: Mass Balancementioning
confidence: 82%
“…Similarly, hydroelectric power generation is impacted by hydrology and geomorphology. In contrast, energy sources derived from biomass do not face any of these shortcomings [2]. Biomass is plant or animal material that can be used (1) to generate electrical or thermal energy, or (2) as the raw material in various industrial manufacturing processes [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process parameters were selected in accordance to different literature reports [3,25,26], which concluded that a 1:8 ratio enhances the decomposition reaction, which leads to a higher mass loss and heating value when compared to lower ratios. Additionally, Mohammed et al (2020) [27] reported an optimal HTC process biomass/water ratio of 0.114 (~1:8) for lignocellulose waste biomass. According to Mäkelä et al (2015), [10] reaction temperature governs HTC reactions and has 3-7 times more effect on the products' properties than residence time; thus, the scope of this article focused on the temperature effect of the HTC on the studied samples.…”
Section: Hydrothermal Carbonizationmentioning
confidence: 99%
“…After analyzing the results of the one-factor experiment, response surface methodology (RSM) was adopted to establish the relationship between CU (Christiansen's uniformity coefficient) values and three factors based on the analysis results of the one-factor experiment. Response surface methodology (RSM) is a collection of mathematical and statistical techniques for investigating the problems in which several independent variables have on response variables [21,22]. RSM aims at building a regression model (approximation) that is closest to the true regression model.…”
Section: Experiments Set-upmentioning
confidence: 99%